2010
DOI: 10.1098/rspb.2010.0344
|View full text |Cite
|
Sign up to set email alerts
|

Storms drive altitudinal migration in a tropical bird

Abstract: Although migration is a widespread and taxonomically diverse behaviour, the ecological factors shaping migratory behaviour are poorly understood. Like other montane taxa, many birds migrate along elevational gradients in the tropics. Forty years ago, Alexander Skutch postulated that severe storms could drive birds to migrate downhill. Here, we articulate a novel mechanism that could link storms to mortality risks via reductions in foraging time and provide, to our knowledge, the first tests of this hypothesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
143
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 132 publications
(154 citation statements)
references
References 40 publications
8
143
0
1
Order By: Relevance
“…Differences between years in dD values are consistent with the costs of residency being weather-related [10]. In 2008, when the preceding season was rainier, more individuals abandoned breeding areas, regardless of social status.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Differences between years in dD values are consistent with the costs of residency being weather-related [10]. In 2008, when the preceding season was rainier, more individuals abandoned breeding areas, regardless of social status.…”
Section: Discussionsupporting
confidence: 58%
“…This frugivorous species breeds in montane forests and some, but not all, individuals migrate to lower elevations after breeding [6] (electronic supplementary material). After eliminating alternative hypotheses regarding the causes of altitudinal migration in this community and population [7][8][9], we showed that residents incur physiological costs of high-elevation storms that limit foraging opportunities, compromising condition [10]. Here, we test the hypothesis that partial migration results from these costs being countered by reproductive benefits of residency, with migratory decisions dependent upon mating prospects the following year (electronic supplementary material, figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…Further, it has been shown in adult birds that adverse weather activates the HPA axis and alters behaviour to facilitate survival (Wingfield et al 1983;Silverin 1986;Rogers et al 1993;Breuner & Hahn 2003;Boyle, Norris & Guglielmo 2010).…”
mentioning
confidence: 99%
“…If attack rates vary in seasonally predictable ways, pathogens could also contribute to shaping temporal patterns of fruiting. Finally, because rainfall is a major axis of seasonality in these forests, influencing plant growth (Brearley et al 2007), seed disperser behavior (Boyle et al 2010), and likely pathogen populations, we related precipitation to community-level phenological patterns.…”
mentioning
confidence: 99%